Storytelling and innovative behavior: an empirical study in a Brazilian group. Issue 8 (5th September 2017) - D'Arrigo, Fernanda Pauletto; Robini, Eduardo; Larentis, Fabiano; Camargo, Maria Emilia; Schmiedgen, Peter
Abstract : Purpose: The paper aims to identify the relationship between the use of storytelling and innovative work behavior (IWB) in organizations. Design/methodology/approach: The research took place in a human resource development (HRD) training session for leaders of Alpha Group. In this session, storytelling was adopted to discuss innovation and IWB. Following the training, the leaders completed a questionnaire about the effectiveness of the stories for the construction of knowledge and IWB. Data were collected from 97 leading sectors. Subsequently, data analysis was performed to identify correlations between the aspects. Findings: The paper provides empirical insights about the use of storytelling, the effectiveness of the stories, as well as their relationship with the innovative behavior of sectors leaders in a Brazilian organization. It has identified the relation between effectiveness of stories and level of innovative behavior. Research limitations/implications: Owing to the chosen research approach, the research results cannot be generalized. Because it is a study of a single organization, the results concern to the reality experienced in the organization studied. Therefore, researchers are encouraged to test this relationship in other organizations to contribute to the discussion and practice of innovation in HRD. Practical implications: Stories can contribute to innovative behavior, and innovative behavior contributes to helping understand the stories. HRD practitioners can provide the use of storytelling, combined with other forms of interventions, to enhance IWB to promote collaborative learning culture and work engagement. Originality/value: Previous papers have identified the role of HRD in the development of IWB in organizations. Theoretically, previous papers have also highlighted that storytelling can be a tool for the development of innovative behavior. The paper empirically has tested these contributions, identifying emerging aspects of this relationship.